An analysis of anxiety levels among volleyball athletes during a provincial inter-club tournament in Jakarta, Indonesia - Rea Rizkita Raga; Yunita Lasma (Physical Education and Sports)
Background: Competitive anxiety is a key psychological factor that can significantly affect an athlete's performance. In volleyball, high-pressure situations often lead to anxiety, potentially hindering players' ability to perform optimally.